2017
DOI: 10.1038/s41598-017-10129-z
|View full text |Cite
|
Sign up to set email alerts
|

CD271 determines migratory properties of melanoma cells

Abstract: Melanoma cell expression of the nerve growth factor receptor CD271 is associated with stem-like properties. However, the contributing role of the receptor in melanoma cell migration is elusive. Here, we explored extracranial (skin, soft tissue, lymph node and liver, n = 13) and matched brain metastases (BM, n = 12) and observed a heterogeneous distribution of phenotypically distinct subsets of CD271+ cells. In addition, we observed that CD271 expression gradually rises along with melanoma progression and metas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 56 publications
(81 reference statements)
4
57
0
Order By: Relevance
“…This is an interesting finding and is supported by both the RNA sequencing data as well as the decrease in UI226 cell migration following selumetinib treatment in our 3D collagen assays. CD271 is associated with increased cell migration, invasion, and/or metastasis in several cancers (21,22,50,51). Recent studies have even shown that CD271 regulates "phenotypic switching" in melanoma by decreasing proliferation while simultaneously increasing invasion through two completely independent mechanisms (52).…”
Section: Discussionmentioning
confidence: 99%
“…This is an interesting finding and is supported by both the RNA sequencing data as well as the decrease in UI226 cell migration following selumetinib treatment in our 3D collagen assays. CD271 is associated with increased cell migration, invasion, and/or metastasis in several cancers (21,22,50,51). Recent studies have even shown that CD271 regulates "phenotypic switching" in melanoma by decreasing proliferation while simultaneously increasing invasion through two completely independent mechanisms (52).…”
Section: Discussionmentioning
confidence: 99%
“…[4,5] For example, CM cell expression of the nerve growth factor receptor CD271 is associated with stem-like properties involving the epithelialmesenchymal transition, leading to dissemination and invasion of tumor cells. [6,7] It is also well known that tumor cells express antigens that can be recognized by the immune system, inducing an antitumor response that may affect microenvironment. Among different types of immune cells with specific prognostic significance, including T cells, B cells, NK cells and macrophages, the CD20+ B cells have been proven to play an important part in tumor progression, modulating normal cells in favour of tumor cell survival.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the expression levels of PD-L1 and CD271 on the melanoma cells were both increased by IFN γ such that PD-L1 levels were related to those of CD271, and together with PD-L1 strongly and additively suppressed melanoma specific CTL activation [131] . CD271 expression on melanoma cells has also been linked to p53 activity, the DNA damage response and chemotherapeutic drug resistance as well as migratory properties to form metastases [132][133][134] . The higher expression levels of CD271 may determine specific properties of brain trophic metastatic melanoma cells [135,136] .…”
Section: Cd271 (P75ntr)mentioning
confidence: 99%